Organizational culture and leadership - Schein, Edgar H. (San Francisco : Jossey-Bass, 2010)
Part One: Organizational Culture and Leadership Defined Part Two: The Dimensions of Culture Part Three: The Leadership Role in Building, Embedding, and Evolving Culture Part Four: How Leaders Can Manage Culture Change Part Five: New Roles for Leaders and Leadership
BSBA
Keywords: Corporate culture; Leadership